SPORT CULTURE DEVELOPMENT IN KINDERGARDENS IN NIŠ - Zoran Jonić; Jadranka Kocić; Mirjana Petrović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
In assume that there is insufficient physical angagement in children, insufficient teachers`, parents`, and childs`"sport entelligence", it was decided to realize the project "Communication and culture in sport". Previous aim of project was growing up the health level in children, growing up the level of sport culture, giving educative and entertaining contents to familly, children, and teachers, such as opening kindergardens to local society. To satisfaction and happiness of children, it was find friends which understood ideas and which supported in financial way. At the end of 2007. year it was start to build sport outdoor grass terrains in kindergarden yard ''Cvrčak'' in Niš. It was build athlet track, outdoor mini foodball, basketball and voleyball. After that more interested was sport clubs in town to work with children at their own fields, which contributed greather affirmation an growing health and sport culture level in children. In one year lasted ciclus, sport clubs afirmated their work, showing and training children the bases of sports elements, such as attracted children in sport clubs in cooperation with physical education expert service Office. In that way clubs reached a lot of members, parents had painless favor, teachers varies work contents, and in children it was growen up health and sport culture level. In cooperation with coatches many of them could find and induced tallent to sport activities right choise. It was more intensive cooperated with parents. To many of them it was the first small-great step in sport world